A validated LC–MS/MS method for the quantitative measurement of creatinine as an endogenous biomarker in human plasma. (October 2016) - Zhao, Yue; Liu, Guowen; Angeles, Aida; Christopher, Lisa J; Wang, Zhaoqing; Arnold, Mark E; Shen, Jim X
Background: Creatinine is an endogenous compound generated from creatine by normal muscular metabolism. It is an important indicator of renal function and the serum level is routinely monitored in clinical labs.Results & methodology: Surrogate analyte (d3-creatinine) was used for calibration standard and quality control preparation and the relative instrument response ratio between creatinine and d3-creatinine was used to calculate the endogenous creatinine concentrations.Conclusion: A fit-for-purpose strategy of using a surrogate analyte and authentic matrix was adopted for this validation. The assay was the first human plasma assay using such strategy and was successfully applied to a clinical study to confirm a transient elevation of creatinine observed using an existing clinical assay.